Tumor-Associated Antigens (TAAs) for the Serological Diagnosis of Osteosarcoma - Li, Jitian; Qin, Bo; Huang, Manyu; Ma, Yan; Li, Dongsheng; Li, Wuyin; Guo, Zhiping (Frontiers in Immunology, 2021)
Osteosarcoma (OS) is the most common malignant bone tumor in childhood and adolescence. Although its incidence rate is low among cancers, the prognosis of OS is usually poor. Despite that some biomarkers such as p53 have been identified in OS, the association between the biomarkers and clinical outcome is not well understood. Thus, it is necessary to establish a method to identify patients diagnosed with OS at an early stage. It is becoming obvious that anti-tumor-associated antigens (TAAs) autoantibodies (TAAbs) in sera could be used as serological biomarkers in the detection of many different types of cancers. This notion indicates that TAAbs are considered as immunological “sentinels” associated with tumorigenesis underlying molecular events. It provides new insights into the differential diagnosis of cancers even to the extent that into molecular and cellular biology. What’s more, it is reported that a customized TAA array could increase the sensitivity/specificity significantly. TAA arrays also have great application prospects in detecting cancer in an early stage, monitoring cancer progression, discovering new therapeutic targets, and designing personalized treatment. In this review, we provide an overview of the TAAs identified in OS as well as the possibility that TAAs and TAAbs system be used as biomarkers in the immunodiagnosis and prognosis of OS.